Regional Economic Outlook, April 2016, Sub-Saharan Africa : Time for a Policy Reset. (Regional Economic Outlook, 2016)
Economic growth in sub-Saharan Africa as a whole has fallen to its lowest level in 15 years, though with large variation among countries in the region. The sharp decline in commodity prices has severely strained many of the largest economies, including oil exporters Angola and Nigeria, and other commodity exporters, such as Ghana, South Africa, and Zambia. At the same time, the decline in oil prices has helped other countries continue to show robust growth, including Kenya and Senegal. A strong policy response to the terms-of-trade shocks is critical and urgent in many countries. This report also examines sub-Saharan Africa's vulnerability to commodity price shocks, and documents the substantial progress made in financial develop, especially financial services based on mobile technologies.